Non-monetary benefit sharing mechanisms within the projects funded by the Benefit Sharing Fund - Galluzzi, Gea; López Noriega, Isabel; Halewood, Michael (2014)
This study presents and overview of the projects that have been funded by or proposed to the Benefit-sharing Fund (BSF) under the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPRFA). In particular, the study focusses on the technology transfer, capacity building and information exchange-related activities that are included in those projects. Through the analysis, we address the following issues: - The geographic scope of projects, and the activities and partnerships within them; - The types of technologies, capacities and information being generated and transferred; - The actors involved in the co-development and transfer of technologies, capacities and information); and, - Situations in which technology transfer, capacity building and information exchange are pursued or promoted together as part of a package and when they are pursued or promoted independently of each other